Identification and evaluation of factors influencing sports fan attendance at international events: volleyball case study - Ryśnik, Jakub (Turyzm/Tourism, 2019)
The article presents unpublished results of research conducted among fans at the 2014 FIVB Volleyball Men’s World Championship (1618 respondents to a direct questionnaire survey). Its aim is to describe selected motives and barriers to attendance at international sports events. The analysis attempts to obtain information about the importance of particular factors and barriers for respondents, their relative importance and to derive a model from the correlation between these variables to explain the attendance of fans at international sports events.